Culture of Social Integration: How Extractive Colonialism Promotes Contemporary Individual Income. Issue 4 (23rd February 2023) - Fu, Tong; Li, Yuanyuan; Feng, Dawei
ABSTRACT: By exploring the history of northeastern China in 1898–1911, this paper documents that extractive colonialism spurs a culture of social integration that generates a positive effect on contemporary individual income, with robustness to potential endogeneity bias. Given that the existing literature has emphasized the long-run negative economic impacts of extractive colonialism, this paper helps explain the following institutional puzzle: Why does extractive colonialism spur development in the long run? We thereby deepen understanding of colonialism and institutions from a cultural perspective.